The public governance of collaborative spaces: discourse, design and democracy - Skelcher, Chris; Smith, Mike; Mathur, Navdeep (2005)
This article investigates the relationship between democratic practices and the design of institutions operating in collaborative spaces, those policy and spatial domains where multiple public, private and non-profit actors join together to shape, make the implement public policy. Partnerships are organizational manifestations of institutional design for collaboration. They offer flexibility and stakeholder engagement, but are loosely coupled to representative democratic systems. a multi-method research strategy examines the impact of discourses of managerialism, consociationalism and participation on the design of partnerships in two UK localities. Analysing objective measures of democratic performance in partnerships and interpreting the discursive transition from earlier practices in representative democratic institutions we find that institutional designs for collaboration reflect different settlements between discourses, captured in the distinction between club, agency and polity-forming partnership types. The results show how the governance of collaborative spaces is mediated through a dominant set of discursively defined institgutional practices. - Reproduced.
Keywords: Democracy; Good governance; Public private partnership